58 Histomorphological Study of Epididymis, ductus deferens and phallus in Adult Male Guinea Fowl (Numida meleagris) - Mirhish, Shakir M.; M. Mirhish, Shakir (The Iraqi Journal of Veterinary Medicine, 2019)
This study was conducted to investigate the anatomical, histological characteristic features of epididymis, ductus deferens and phallus of male guinea fowl (Numidia meleagris ). Fifteen healthy male guinea fowl aged between 18-24 months, weighing 1280 - 1405 gram were used in current study which brought from local market in Baghdad governorate. The epididymis of guinea fowl consisted from rete testis, efferent ductless, connecting duct and epididymal duct. The study revealed that the mean diameter of epididymal ducts was 285.17± 2.43µm lined with pseudostratified columnar epithelium. The epididymal duct continuous with ductus deferens which become wider caudally towards the cloaca, the length of right and left ductus deferens were 9.16±1.20 cm and 9.80±1.24cm respectively. The copulatory organ (phallus) of guinea fowl was not well developed and non-intermittent type consist from right and left lateral lymphoid bodies with median eminences, the transverse width 5.01±0.24mm, the cranio-caudal width 3.51±0.07mm and dorso- ventral width 4.32±0.25mm. The lining epithelium of coprodeum was pseudo stratified columnar epithelium. This study concluded that the epididymis of male guinea fowl located on dorsomedial surface of the testes and without definite parts as in domestic animals, the ductus deferens of guinea fowl was tortuous, the phallus of guinea fowl is non - intermittent type.